1988
DOI: 10.1007/bf00496419
|View full text |Cite
|
Sign up to set email alerts
|

Blood sampling in very low birth weight infants receiving different levels of intensive care

Abstract: Sixty very low birth weight infants (birth weight 560-1450 g) were studied during the first 28 days of life. The infants were classified as group A (n = 19 infants who never required ventilator support), group B (n = 20 infants mechanically ventilated for minor respiratory problems), and group C (n = 21 infants ventilated for respiratory distress syndrome). Diagnostic blood sampling was measured, infants were checked for clinical symptoms and laboratory signs of anaemia 24 h before and after the transfusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
5
7

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 32 publications
4
86
5
7
Order By: Relevance
“…Every milliliter of blood loss represents a loss of 0.35-0.5 mg iron (assuming an Hb concentration of 10-15 g/dl). In very low-birthweight infants, iron losses due to phlebotomy can amount up to 6 mg/kg/week [75]. Therefore, it is desirable to search for a method to measure iron status without causing additional blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Every milliliter of blood loss represents a loss of 0.35-0.5 mg iron (assuming an Hb concentration of 10-15 g/dl). In very low-birthweight infants, iron losses due to phlebotomy can amount up to 6 mg/kg/week [75]. Therefore, it is desirable to search for a method to measure iron status without causing additional blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…These transfusions are given to replace losses due to diagnostic sampling and to treat the physiologic decline in H b concentration designated the anemia of prematurity (1)(2)(3). Studies have shown that VLBW infants will receive approximately 50 mL of blood per kg from as many as eight to 10 adult donors during the first month of life (1,3,4). However, recent data suggest that changes in transfusion practices for neonates may reduce donor exposure (5,6).…”
mentioning
confidence: 99%
“…The aetiology is multifactorial and includes especially iatrogenic blood losses due to laboratory examinations [1][2][3], a lack of erythropoietin [2,[4][5][6], and a lack of nutritive factors [7,8]. However, the reduction of iatrogenic blood losses [9,10], prophylactic iron substitution [11], the use of recombinant human erythropoietin, and placentofetal blood transfusion after delayed cord clamping have reduced but not dispensed with the need for transfusions during the first weeks of life [12,13].…”
Section: Introductionmentioning
confidence: 99%